The Normal Personality a new way of thinking about people - Reiss, Steven (Cambridge University Press, 2013)
Psychodynamic theorists have regarded personality as those behaviors we engage in that most resemble symptoms of mental illness. To appreciate the extent to which psychologists have derived personality traits from theories of mental illness, please compare the following two lists. On the left are the original ten traits assessed by theMinnesotaMultiphasicPersonality Inventory(MMPI;Hathaway& McKinley, 1943). Notice the extent to which theMMPI personality traits read like a list of mental illnesses. On the right are examples of the “normal” personality traits discussed in this book